Supplementation of Vitamin A and D in the Medication of Lung Tuberculosis - Rita Dian Pratiwi; Dibyo Pramono; Iswanto Iswanto; Junaedi Junaedi (International Journal of Public Health Science (IJPHS), 2017)
At District of Wonosobo, Indonesia incidence rate of lung tuberculosis(TB) is increasing over years. In 2011 sputum conversion rate had reached 83.8%. Incidence rate of lung TB is still relatively high. This is influenced by many factors, one of which is the process of transmission. Potential of transmission may still occur until end of intensive medication (2 months). Vitamin A and D as immunoprotection can be used as supplements that can accelerate sputum conversion. To find out effect of vitamin A and D supplementation in accelerating sputum conversion of lung TB patients during intensive phase. The study was true experimental (double blinded randomized controlled trial). Subject of the study consisted of two groups; one comprised as many as 30 positive acid fast bacillus lung TB patients supplemented with vitamin A at dosage of 1 x 5000 IU/day and vitamin D at dosage of 1 x 400 IU/day whereas another group was placebo during intensive phase. There was effect of vitamin A and D supplementation to acceleration of sputum conversion with score of p 0.003; HR 2.45. Sputum conversion acceleration occurred in the experiment group during the second week with vitamin A and D supplementation as much as 86%. Vitamin A and D supplementation could accelerate the incidence of sputum conversion as much as 2.45 times greater than placebo group; thus vitamin A and D could be used as complementary supplements in the medication of lung TB medication during intensive phase.